Response of Growth, Albumin, and Blood Glucose of Snakehead (Channa Striata) Juvenile Feed with the Addition of Different Animal Protein Sources - Novalina Serdiati; Muhammad Safir; Umul Rezkiyah; R Adharyan Islamy (Jurnal Penelitian Pendidikan IPA, 2023)
Snakehead fish or Channa Striata is a type of freshwater fish that has high economic value in Indonesia. Aims of this study was to evaluating the effect of adding different protein sources to snakehead fish feed on fish growth, blood glucose levels, and albumin content of snakehead fish (Channa Striata). This study consisted of 3 treatments and each was given 6 replications. Treatment A: Use of feed made from nilem fish flour. Treatment B: Use of feed made from golden snail flour and Treatment C: Use of feed made from earthworm flour. The best daily growth was obtained by using feed containing animal protein sources from earthworm flour of 1.85 g. The albumin level of snakehead fish at the end of rearing was highest in the treatment using feed made from earthworm flour (5.106%). followed by golden snail flour (4.802%) and nilem fish meal (4.492%). Snakehead fish blood glucose levels 2 hours after consuming the feed increased in all treatments, with the highest value in the treatment of golden snail flour and earthworms (112 mg/dL). Followed by nilem fish meal (105 mg/dL). However blood glucose levels 4 hours after consuming the feed decreased in all treatments. With the highest reduction occurring in the treatment using earthworm flour (38 mg/dL). Followed by golden snail flour (58 mg/dL) and nilem fish meal (92 mg/dL).